PENGEMBANGAN 24 DESTINASI WISATA BAHARI KABUPATEN ENDE - Gadi Djou, Josef Alfonsius (Jurnal Kawistara, 2013)
There are 24 marine tourism destinations in Ende District that have not been managed well enough. To improve tourism development, some management strategies should be taken by stakeholders. First, the government should make some policies that give opportunities and easy access to stakeholders. Scond, the government should make a development planning for the potential destinations. Third, they should make plans that would give information about the most potential destination. Fourth, the government and marine communities should prepare human resource in management. At last, the government should promote those marine tourism destinations continuosly.